Effect of ion doping in silica-based nanoparticles on the hemolytic and oxidative activity in contact with human erythrocytes. (25th February 2020) - Tsamesidis, Ioannis; Pouroutzidou, Georgia K.; Lymperaki, Evgenia; Kazeli, Konstantina; Lioutas, Christos B.; Christodoulou, Evi; Perio, Pierre; Reybier, Karine; Pantaleo, Antonella; Kontonasaki, Eleana
Abstract: Aim: The aim of this study was the synthesis of ion doped silica-based nanoparticles and the evaluation of their toxic effect on erythrocytes. Materials & methods: Their synthesis was performed using the sol-gel method, by the progressive addition of calcium, magnesium and copper ions on pure silica nanoparticles. The toxicity evaluation was based on hemolysis, lipid peroxidation, ROS, H2 O2 species and antioxidant enzyme production. Results: The addition of Mg and Cu in the SNs presented better hemocompatibility by protecting erythrocytes from oxidative stress. Conclusion: Ion doping with magnesium in the investigated calcium silicate system induces a protective effect in erythrocyte membrane in compare with pure silica nanoparticles. Highlights: Addition of Mg and Cu in SNs improved their hemocompatibility. All SNs-concentrations lower than 0.125 mg/mL are hemocompatible. Ion doping in SNs protected erythrocytes from oxidative stress. Higher amount of H2 O2 species(detected by LC/MS) have been generated in un-doped SNs.